The Effect of Strategic Compensation, HR Development and Work Motivation on Vocational High School Teacher Performance. - Abdurrahman Sadikin; Lenny Nuraeni; Muthia Mutmainnah; Ika Yuniwati; Apriani Riyanti (Departement of Mathematics Education, 2023)
The goals of this research are to look at the connection between performance and human resource development, compensation, and motivation. Private schools were used for this study. The research sample was taken from 42 private school teacher respondents. Quantitative research is the kind of study being conducted. For this study's data analysis, several types of linear regression were applied. The findings of the study reveal that salary and motivation both have a substantial impact on the performance of teachers in private schools. This is indicated by the human resource development variable. Partly, motivation has a substantial effect on teacher performance in private schools with a significance level of less than 0.05 or 5%, whereas human resource development and compensation have no meaningful impact